Development of Brake Camp Material Using Reinforced Polymer Composite by Clamshells/Cardboard Waste/Orange Peel - Isma Wulansari; Diva Pahlevi Putra Aumee; Muhammad Seprianto; Fitria Ika Aryanti; Untung Prayudie (Jurnal Inotera, 2024)
Brake pads are equipment that uses synthetic friction resistance and is then used on a rotating machine to reduce or stop speed. It is necessary to develop brake pad materials that are more environmentally friendly and can be commercialized. Clamshells containing calcium carbonate (CaCO3), cardboard waste, and orange peel containing cellulose can also be used as alternatives in developing brake pad materials that are more environmentally friendly compared to asbestos brake pads. This research aims to determine the optimal composition for developing reinforcing polymer composites for brake pad materials. The methods used in this research include microscopy test analysis, degree of swelling, and tensile strength. The test results show that variation II shows a clearer surface appearance with a low degree of swelling of 0 – 0.17%, so variation II is appropriate for application as a brake pad material. The tensile strength test results show a maximum tensile strength of 6.521 Mpa